British Women's Writing, 1930 to 1960 Between the Waves - Kennedy, Sue; Thomas, Jane (Liverpool University Press, 2023)
This volume contributes to the vibrant, ongoing recuperative work on women's writing by shedding new light on a group of authors commonly dismissed as middlebrow in their concerns and conservative in their styles and politics. The neologism 'interfeminism' - coined to partner Kristin Bluemel's 'intermodernism' - locates this group chronologically and ideologically between two 'waves' of feminism, whilst also forging connections between the political and cultural monoliths that have traditionally overshadowed them. Drawing attention to the strengths of this 'out-of-category' writing in its own right, this volume also highlights how intersecting discourses of gender, class and society in the interwar and postwar periods pave the way for the bold reassessments of female subjectivity that characterise second and third wave feminism.   The essays showcase the stylistic, cultural and political vitality of a substantial group of women authors of fiction, non-fiction, drama, poetry and journalism including Vera Brittain, Storm Jameson, Nancy Mitford, Phyllis Shand Allfrey, Rumer Godden, Attia Hosain, Doris Lessing, Kamala Markandaya, Susan Ertz, Marghanita Laski, Elizabeth Bowen, Edith Pargeter, Eileen Bigland, Nancy Spain, Vera Laughton Matthews, Pamela Hansford Johnson, Dorothy Whipple, Elizabeth Taylor, Daphne du Maurier, Barbara Comyns, Shelagh Delaney, Stevie Smith and Penelope Mortimer. Additional exploration of the popular magazines Woman's Weekly and Good Housekeeping and new material from the Vera Brittain archive add an innovative dimension to original readings of the literature of a transformative period of British social and cultural history.   List of contributors: Natasha Periyan, Eleanor Reed, Maroula Joannou , Lola Serraf, Sue Kennedy, Ana Ashraf, Chris Hopkins, Gill Plain, Lucy Hall, Katherine Cooper, Nick Turner, Maria Elena Capitani, James Underwood, and Jane Thomas.